GEOLOGI DAN PALEONTOLOGI FORMASI BALANGBARU DAN FORMASI MARADA BERUMUR KAPUR, SULAWESI SELATAN - Fauzie Hasibuan; Alex Limbong (Pusat Survei Geologi, 2009)
A geological and paleontological studies on the Balangbaru and Marada Formations has been carried out. Both formations show that their depositional environment was in basin with turbidity currents. Marada Formation can be correlated with Panggalungan Member of the distal part of the Balangbaru Formation. Paleontological study on the Balangbaru Formation has yielded some macrofossils such as echinoid, bivalve Inoceramus sp., ammonite Grossouvreites sp. Marada Formation contains trace fossil Spirorhaphe sp. and species of nannoplankton have been extracted from the shale e.g. Ceratolithoides aculeus, C. kamptneri, Lucianorhabdus cayeuxii, L. arcuatus, L. maleformis, Micula murus, M. concava Lithraphidites quadratus, and Prediscosphaera sp. Based on the presence of macrofossils, nannoplankton, and radiolarian fossils of previous workers it can be concluded that the deposition of the Balangbaru and Marada Formations was in Albian to Maastrichtian (Late Early Cretaceous to Late Cretaceous) time. Keywords: echinoid, bivalvia, ammonite, trace fossil, nannoplankton, radiolarian turbidite